Stereotactic Radiosurgery for Brainstem Metastases: An International Cooperative Study to Define Response and Toxicity - Trifiletti, Daniel M; Lee, Cheng-Chia; Kano, Hideyuki; Cohen, Jonathan; Janopaul-Naylor, James; Alonso-Basanta, Michelle; Lee, John Y K; Simonova, Gabriela; Liscak, Roman; Wolf, Amparo; Kvint, Svetlana; Grills, Inga S; et al. (International journal of radiation oncology, biology, physics, 2016)
PURPOSE: To pool data across multiple institutions internationally and report on the cumulative experience of brainstem stereotactic radiosurgery (SRS). METHODS AND MATERIALS: Data on patients with brainstem metastases treated with SRS were collected through the International Gamma Knife Research Foundation. Clinical, radiographic, and dosimetric characteristics were compared for factors prognostic for local control (LC) and overall survival (OS) using univariate and multivariate analyses. RESULTS: Of 547 patients with 596 brainstem metastases treated with SRS, treatment of 7.4% of tumors resulted in severe SRS-induced toxicity (grade ≥3, increased odds with increasing tumor volume, margin dose, and whole-brain irradiation). Local control at 12 months after SRS was 81.8% and was improved with increasing margin dose and maximum dose. Overall survival at 12 months after SRS was 32.7% and impacted by age, gender, number of metastases, tumor histology, and performance score. CONCLUSIONS: Our study provides additional evidence that SRS has become an option for patients with brainstem metastases, with an excellent benefit-to-risk ratio in the hands of experienced clinicians. Prior whole-brain irradiation increases the risk of severe toxicity in brainstem metastasis patients undergoing SRS.
Keywords: kraniální ozáření; dospělí; Sex Distribution; Female; rozložení podle pohlaví; Adult; výsledek terapie; ženské pohlaví; Radiation Injuries; komorbidita; lidé; nádory mozkového kmene; Causality; Comorbidity; celková dávka radioterapie; Treatment Outcome; Aged, 80 and over; míra přežití; kauzalita; International Cooperation; Risk Factors; radiochirurgie; retrospektivní studie; Radiosurgery; Age Distribution; Male; radiační poranění; Cranial Irradiation; Aged; věkové rozložení; rizikové faktory; Survival Rate; lidé středního věku; Radiotherapy Dosage; senioři nad 80 let; mezinárodní spolupráce; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; vztah dávky záření a odpovědi; Brain Stem Neoplasms; Dose-Response Relationship, Radiation; Humans